TINJAUAN HUKUM TERHADAP TINDAK PIDANA PENGANIAYAAN HEWAN STUDI KASUS : PERDAGANGAN DAGING ANJING DITOMOHON SULAWESI UTARA - Cika Agia Wulandari, - (2019)
Tomohon Market is famous as an extreme market that sells exotic animals meat, such as wild boars, snakes, rats, and bat species, including animals that are considered by most people as companion animals, such as dogs and cats. This is interesting because dogs are not food, but dogs are companion animals as known as pets. The way to slaughter a dog is certainly not in accordance with animal welfare. The study entitled "Legal Review of Criminal Acts on Animal Cruelty (Case: Dog Meat Trade at Tomohon North Sulawesi)" has two formulations, those are how the legal review of animal cruelty that happened on the the dog meat trade at Tomohon North Sulawesi and how the legal review about the dog meat trade. The purpose of this study is to find out the legal review of animal cruelty and dog meat trade. This study uses a descriptive empirical normative method. The data sources are primary and secondary data from press releases, as well as data informed by the Animal Lovers Community, Ministry of Health and Veterinarians in Indonesia. The theories used in this case are the law enforcement and the law protection. Based on the data analysis, it can concluded that the dog meat trade at Tomohon North Sulawesi is a criminal act of animal cruelty which is against the law. Not only affected to the animals, the dog meat trade also have negative impact on human health. Evidenced by the high number of fatalities caused by rabies in North Sulawesi